Assessment of Benthic Macro-Invertebrates of Freshwater Ecosystem: A Case Study of Ovia River (Iguoriakhi), Edo State, Nigeria - Iyagbaye, Louis A.; Iyagbaye, Rich O.; Omoigberale, Michael O. (European Scientific Journal, ESJ, 2017)
In this study, the diversity and seasonal variation of benthic macro-invertebrates of Ovia River (Iguoriakhi), Edo State, Southern Nigerian, were studied between July, 2014 and February, 2015. Four stations were selected and sampled monthly and investigated for benthic macro-invertebrates’ community structure using basic statistical measurement of abundance and diversity indices to characterize the benthic macro invertebrates. The species richness, evenness and diversity of the benthic macro-invertebrates in the study area were high and typical of a tropical fast-flowing freshwater river. There was a total of 45 taxa, made up of 1,135 individuals; 10 Ephemeroptera, 10 Diptera, 7 Coleoptera, 7 Odonata, 4 Hemiptera, plasiopora, Haplotaixa, Decapoda, Hydrachnellae, Lepidoptera, Gastropoda, and Trichoptera were represented with a taxa each. The dominant taxa include Ephemeroptera, while the Diptera was the only sub-dominant order identified. Analysis of Variance (ANOVA) revealed that the overall density was significantly different (P<0.05) in the study stations. A posteriori Duncan Multiple Range (DMR) test indicated that the abundance of Dipterans and Ephemeropterans at station 2 and 4 respectively were the source of the significant difference. The EPT to total ratio indicated that the water quality of all the studied stations were non impacted. The study concluded that benthic macro-invertebrates are good candidate and less expensive indices for water quality monitoring.